2020
DOI: 10.1021/acssuschemeng.0c04719
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Hierarchical MoSe2/N, F Co-Doped Carbon Heterostructure Assembled by Ultrathin Nanosheets for Advanced Lithium-Ion Batteries

Abstract: MoSe2 has attracted great interest as an anode material for lithium-ion batteries (LIBs) thanks to its high capacity. Nevertheless, the poor cycle performance caused by the huge volume change during the lithiation/delithiation process seriously limits its practical application in LIBs. Herein, a 3D hierarchical MoSe2/N, F co-doped carbon (MoSe2/NFC) heterostructure is prepared via a simple method. Notably, the N, F co-doped heterostructure can expand the (002) plane of MoSe2, which contributes in facilitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In recent years, substantial efforts have been made to develop the new anodes with high power/energy density and superior cycling life for LIBs. Metal selenides, such as MoSe 2 , [1][2] CoSe x , [3][4] WSe 2 , [5] SnSe 2 [6][7] and GeSe 2 , [8][9] have received much attention owing to their rich redox chemistry, high specific capacities and better electrical conductivity compared to their oxide counterparts. On the other hand, the weaker bonding of metal-selenium improves the reversibility of the conversion reaction during the charge and discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, substantial efforts have been made to develop the new anodes with high power/energy density and superior cycling life for LIBs. Metal selenides, such as MoSe 2 , [1][2] CoSe x , [3][4] WSe 2 , [5] SnSe 2 [6][7] and GeSe 2 , [8][9] have received much attention owing to their rich redox chemistry, high specific capacities and better electrical conductivity compared to their oxide counterparts. On the other hand, the weaker bonding of metal-selenium improves the reversibility of the conversion reaction during the charge and discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…In Li or Na ion batteries, it has been reported that the energy storage mechanism of MoSe 2 electrode is the mixed reaction of intercalation reaction and conversion reaction [20,35] . During the discharge process, Li x MoSe 2 is formed by the intercalation of Li ions into MoSe 2 , and then Li x MoSe 2 is reduced to Mo and Li 2 Se with the progress of discharge.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, such features give the MoSe 2 great potential as cathode material for metal‐ion batteries, which enable fast charge and ion transfer during charge/discharge process [17,18] . So far, there have been a number of works with regard to the MoSe 2 based electrode materials for metal‐ion batteries, such as carbon‐stabilized MoSe 2 nanosheets for the sodium ion batteries (SIBs), [19] hierarchical MoSe 2 /N, F co‐doped carbon heterostructure for the lithium ion batteries (LIBs), [20] hierarchical MoSe 2 hollow spheres for the LIBs [21] . However, there are few reports on the MoSe 2 based electrodes for Mg or Mg/Li ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy takes the advantage of the unchanged material crystal structure, and the original excellent properties can be reflected in the recombination process. Hybridization process consists of a variety of materials, mainly carbon-based materials such as graphene and CNTs, as well as some monocrystalline silicon, oxides, and sulfides. Li et al reported the SN-G/Si composite material synthesized by S–N co-doped graphene and nanosilicon particles (Figure a–c). The SN-G/Si for LIBs could provide a high capacity of 2020 mAh g –1 , and the Coulombic efficiency was close to 97% (Figure d).…”
Section: Strategies For Improving Electrochemical Properties Of 2d Ma...mentioning
confidence: 99%